'Captiva' St. Augustinegrass - Laurie E. Trenholm; Kevin Kenworthy (EDIS)
ENH1137, a 2-page illustrated fact sheet by L. E. Trenholm and Kevin Kenworthy, introduces this new dwarf cultivar characterized by dark green, short, narrow leaf blades and improved tolerance to southern chinch bugs and plant hoppers, that is now available for use in landscapes. Published by the UF Department of Environmental Horticulture, December 2009.